Pemberdayaan Kader Posyandu untuk Pencegahan Risiko HIV/AIDS di Kecamatan Cimaragas - Nida Solihatul Masruroh; Emilia Kartika Ana; Restu Sugiharti; Anggi Dwi Yulia; Dimas Irawan; Kiki Hamdani; Adi Nurapandi (Yayasan Inspirasi El Burhani, 2022)
Introduction: The existence of Posyandu in the community has a very large and important role, because it is related to the fulfillment of very important health needs for mothers and children. Health matters are a factor that has an important role to create high-quality human resources. HIV/AIDS is the seventh disease from the third health priority. Objective: Aims as a health promotion activity to provide knowledge to posyandu cadres through health education about preventing the risk of HIV/AIDS, in order to avoid the transmission and spread of HIV/AIDS. Metod: This study uses the method of health education on HIV/AIDS and the use of leaflet print media. This health education promotion was carried out at the Melati IV Posyandu in Totokan Village, Cimaragas District, Ciamis Regency, on March 21, 2022. By going through several stages, namely the selection of places and targets, preparation of facilities and infrastructure, implementation of activities, and finally evaluation. Result: The result of the implementation of this health education promotion is the implementation of health education regarding the prevention of the risk of HIV/AIDS in Cimaragas District, before being given counseling there were several respondents who knew about HIV/AIDS but did not understand the disease, but after being given the knowledge and ways to prevent it, it showed that respondents can understand the importance of preventing the risk of HIV/AIDS, Conclussion: The conclusion of the health education activities regarding the prevention of HIV/AIDS risk which was carried out to posyandu cadres in Cimaragas sub-district, could increase knowledge and understanding of HIV/AIDS risk prevention, this health education event ran smoothly.